Clinical and laboratory tests for the diagnosis of heparin-induced thrombocytopenia - Nagler, Michael; Bakchoul, Tamam (Thrombosis and Haemostasis, 2016)
A rapid diagnostic work-up is required in patients with suspected heparin-induced thrombocytopenia (HIT). However, diagnosis of HIT is challenging due to a number of practical issues and methodological limitations. Many laboratory tests and a few clinical scoring systems are available but the individual characteristics and the diagnostic accuracy of these are hard to appraise. The 4Ts score is a well evaluated clinical assessment tool with the potential to rule out HIT in many patients. Still, it requires experience and is subject to a relevant inter-observer variability. Immunoassays such as enzyme-linked immunosorbent assays or recently developed rapid assays are able to exclude HIT in a number of patients. But, accuracy of immunoassays differs depending on type of assay, threshold, antibody specificity and even manufacturer. Due to a comparatively low positive predictive value, HIT cannot be confirmed by immunoassays alone. In addition, only some of them are immediately accessible, particularly in small laboratories. While functional assays such as the serotonin release assay (SRA) and the heparin-induced platelet activation assay (HIPA) are considered as gold standard for diagnosis of HIT, they require a highly specialised laboratory. In addition, some of them are not adequately evaluated. In clinical practice, we recommend an integrated diagnostic approach combining not only clinical assessment (the 4Ts score) but immunoassays and functional assays as well. We propose a clear diagnostic algorithm supporting clinical decision-making. Furthermore, we provide an overview of all current laboratory techniques for HIT and discuss diagnostic pathways and strategies to reduce diagnostic errors, and future perspectives.
Keywords: Heparin/adverse effects; immunoassay/methods; thrombocytopenia/chemically induced; thrombocytopenia/diagnosis